The role of FDG-PET/CT imaging in early detection of extra-cardiac complications of infective endocarditis. (January 2015) - Orvin, K.; Goldberg, E.; Bernstine, H.; Groshar, D.; Sagie, A.; Kornowski, R.; Bishara, J.
Abstract: The exact incidence of extra-cardiac complications (ECC) in patients with infective endocarditis (IE) is unknown but presumed to be high. These patients, although mostly asymptomatic, may require a more aggressive therapeutic approach. 18 fluorodeoxyglucose–positron emission tomography/computed tomography (FDG-PET/CT) is used for the diagnosis of infections, but its role in the early diagnosis of IE complications is still unclear. This study aimed to evaluate the role of FDG-PET/CT in the early diagnosis of ECC in IE and its implications for medical management. We prospectively studied 40 consecutive patients with a confirmed diagnosis of IE (according to the modified Duke criteria) who underwent a whole body FDG-PET/CT study within 14 days from diagnosis. The FDG-PET/CT demonstrated ECC in 17 (42.5%) patients, while 8 (38.1%) of them were asymptomatic. The most frequent embolic sites were musculoskeletal and splenic. Owing to the FDG-PET/CT findings, treatment planning was modified in 14 (35%) patients. This included antibiotic treatment prolongation (27.5%), referral to surgical procedures (15%) and, most substantially, prevention of unnecessary device extraction (17.7%). According to our experiences, FDG-PET/CT imaging was useful in the detection of embolic and metastatic infections in IE. This clinical information had a significant diagnostic and therapeutic impact in managing IE disease.